Insecurity and Foreign Direct Investment in Nigeria - Adesegun, Owolabi; Olumide, Ayenakin Olabanjo (International Journal of Sustainable Development & World Policy, 2015)
Nigeria has joined the league of countries that spend a higher proportion of their budgetary allocation on security. Thus, this paper empirically investigates the impact of insecurity on foreign direct investment (FDI) covering the period of 2003 to 2012. The study employed Least Square technique (OLS) to analyze the secondary data collected from Central Bank of Nigeria Statistical bulletin of various issues. Vote on security and defense (VSD) was used as a proxy for insecurity. The paper reveals a negative relationship between Foreign Direct Investment (FDI) and insecurity. The paper recommends that strong policy stance must be taken to address the state of insecurity in Nigeria so as to attract more foreign direct investment essential for economic growth and development.